Analysis of the Implementation of the Work Accident Insurance Program at the Office of BPJS Ketenagakerjaan, Binjai Branch - Elsa Zulfita; Wahyu Syarvina (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2022)
This study aims to determine how the implementation of the Work Accident Insurance program at the Office of BPJS Employment Binjai Branch and its obstacles. The sample of this research is the BPJS Employment Office of the Binjai Branch. In this study, using qualitative methods with data collection techniques using literature studies, observation and documentation studies. The results of this study indicate that the implementation of the Work Accident Insurance program at the BPJS Employment Office of the Binjai Branch has been carried out properly and in accordance with applicable regulations. However, there are several obstacles that hinder the smooth implementation of this program, such as time management, technology and the role of the community.